Atomic Force Microscopy: A Powerful Tool to Address Scaffold Design in Tissue Engineering - Marrese, Marica (J Funct Biomater, 2017)
Functional polymers currently represent a basic component of a large range of biological and biomedical applications including molecular release, tissue engineering, bio-sensing and medical imaging. Advancements in these fields are driven by the use of a wide set of biodegradable polymers with controlled physical and bio-interactive properties. In this context, microscopy techniques such as Atomic Force Microscopy (AFM) are emerging as fundamental tools to deeply investigate morphology and structural properties at micro and sub-micrometric scale, in order to evaluate the in time relationship between physicochemical properties of biomaterials and biological response. In particular, AFM is not only a mere tool for screening surface topography, but may offer a significant contribution to understand surface and interface properties, thus concurring to the optimization of biomaterials performance, processes, physical and chemical properties at the micro and nanoscale. This is possible by capitalizing the recent discoveries in nanotechnologies applied to soft matter such as atomic force spectroscopy to measure surface forces through force curves. By tip-sample local interactions, several information can be collected such as elasticity, viscoelasticity, surface charge densities and wettability. This paper overviews recent developments in AFM technology and imaging techniques by remarking differences in operational modes, the implementation of advanced tools and their current application in biomaterials science, in terms of characterization of polymeric devices in different forms (i.e., fibres, films or particles).